Itinerário de leitura de contos literários : um estudo léxico-sintático por intermédio da lexicologia e linguística de córpus - (:unkn) unknown (Universidade Estadual de Goiás, 2023)
Considering that reading practice can promote the development of linguistic and cultural competencies, we developed a linguistic-computational analysis on a corpus composed exclusively of Brazilian literary short stories. Our overall objective is to propose the creation of a Literary Short Stories Reading Itinerary based on lexicalsyntactic metric calculations. Our specific objectives are: 1) To construct a representative corpus of literary short stories; 2) To identify the lexical-syntactic profile of the literary short stories; 3) To organize the works based on the level of linguistic complexity; 4) To apply a perception questionnaire to students in the second phase of Elementary School. For the theoretical-methodological foundation, we will use Lexicology (ANTUNES, 2018; BIDERMAN, 1998, 2001; COSSON, 2014), Corpus Linguistics (BERBER SARDINHA, 2004, 2012; BIBER; REPPEN, 2015; HUNSTON (2022), and Interculturality (BARBOSA, 2009, SARMENTO, 2004). We constructed a corpus with 878 Brazilian literary short stories by 78 authors and 1,556,749 words. The processing was carried out by the NILC-Metrix platform (NILC, 2021). Finally, a multiple-choice questionnaire was applied to students in the second phase of Elementary School. Our classification of the level of complexity, based on the software data, was as follows: "very easy" (5 short stories); "easy" (211 short stories); "moderate" (484 short stories); "difficult" (160 short stories); and "very difficult" (18 short stories). Furthermore, the classification attributed to the short stories by the students, obtained through the questionnaire, was similar, varying on average 4 points in relation to the software results. This empirical classification highlights the potential of our itinerary as an auxiliary tool for teachers in selecting short stories appropriate to the students' level, becoming a pedagogical reference for Portuguese language classes. In this way, a double intervention is promoted: reading practice and exposure to varied literary short stories in lexical-syntactic terms.
Literary short story reading itinerary: a lexico-syntactic study through lexicology and corpus linguistics
Keywords: Contos; Linguística de Corpus; NILC-Metrix; Métricas léxico-sintáticas; Linguística de corpus; Short stories; Lexical-syntactic metrics; Corpus linguistics; LINGUISTICA, LETRAS E ARTES